A high accuracy measurement of CH4 and CO2 using system state parameter equivalence correction method - Liu, Yebo; Li, Xiaofeng; Chen, Jiayuan; Du, Liang; Lu, Pengcheng; Chen, Chen (Frontiers in Physics, 2025)
To enable to achieve high performance measurement of CH4 and CO2 gases in the field environment, a measuring system using infrared tunable diode laser absorption spectroscopy (TDLAS) technology was proposed in this paper. The measuring system adopted an infrared compact-linear optical structure, including two infrared distributed feedback (DFB) lasers (central wavelength at 2,325 nm and 2004 nm, respectively), long optical path multi-pass cell (effective optical path is 41.5 m) and photoelectric detectors (response wavelength is from 900 nm to 2,600 nm). Combining system state parameter equivalence correction (SSPEC) method to eliminate of measuring system error. The experimental results show that the minimum detection limit (MDL) of CH4 and CO2 are 0.29 ppmv@29s and 6.5 ppmv@17s, the measurement uncertainty is 2.4‰ and 2.5‰ with 98% confidence interval, the maximum measurement errors are 2.3‰ and 2.5‰. Finally, the environmental adaptability test was carried out in the seismic station of Jilin Province, P.R. China. Compared with the international measuring system, the measurement performance of the proposed system is better.